2010
DOI: 10.1007/s00284-010-9848-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Biodiversity of Endophytic Fungi in Dendrobium devonianum and Dendrobium thyrsiflorum from Vietman

Abstract: Endophytic fungi are rich in orchids and have great impacts on their host plants. 53 endophytes (30 isolates from Dendrobium devonianum and 23 endophytic fungi from D. thyrsiflorum) were isolated, respectively, from roots and stems of Dendrobium species. All the fungi were identified by way of morphological and/or molecular biological methods. 30 endophytic fungi in D. devonianum were categorized into 11 taxa and 23 fungal endophytes in D. thyrsiflorum were grouped into 11 genera, respectively. Fusarium was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 29 publications
4
63
0
Order By: Relevance
“…Of all the Ascomycetes obtained, 71% of the fungal endophytes belonged to the genus Fusarium. These results correlate with those obtained from a study by Bai et al (2009), Chen et al (2010 and Xing et al (2011) which demonstrated that the dominant fungal endophyte strains isolated so far belong to the genus Fusarium. Although, Fusarium spp.…”
Section: Isolation and Identification Of The Fungal Endophytessupporting
confidence: 82%
“…Of all the Ascomycetes obtained, 71% of the fungal endophytes belonged to the genus Fusarium. These results correlate with those obtained from a study by Bai et al (2009), Chen et al (2010 and Xing et al (2011) which demonstrated that the dominant fungal endophyte strains isolated so far belong to the genus Fusarium. Although, Fusarium spp.…”
Section: Isolation and Identification Of The Fungal Endophytessupporting
confidence: 82%
“…Fungal diversity and richness in different tissues were measured and quantified using a variety of indices 14,18 , including species richness and evenness, Shannon's diversity and Simpson's diversity, dominance and Fisher's alpha diversity.…”
Section: Estimation and Quantification Of Fungal Diversitymentioning
confidence: 99%
“…For the molecular identification, fungal genomic DNA was extracted from the mycelia using peqGOLD Fungal DNA Mini Kit (Peqlab, Erlangen, Germany). The internal transcribed spacer (ITS) region of rDNA genes was amplified using universal eukaryotic primers 14 : ITS1 (5-TCC GTA GGT GAA CCT GCG G-3) and ITS4 (5-TCC TCC GCT TAT TGA TAT GC-3). Standard PCR reactions were performed following the routine protocol and PCR products were directly sequenced.…”
Section: Isolation and Identification Of Endophytic Fungimentioning
confidence: 99%
“…Drug resistance in fungi is increasing and is becoming a serious concern and the high use and misuse of antifungal as probably the main cause of this situation. Therefore, there is an urgent need to search for effective new antifungal agents in treatment of infectious diseases at present (Xing et al, 2011).…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%